Pengaruh Kompetensi terhadap Kinerja Pegawai Negeri Sipil dengan Disiplin Kerja sebagai Variabel Intervening pada Dinas Pendidikan Pemuda dan Olahraga Kabupaten Tambrauw - Solossa, Eduard; Tubagus Ismail; Agus Joko Purwanto3 (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of competence on the performance of Civil Servants (PNS), with work discipline as an intervening variable, at the Tambrauw Regency Education, Youth, and Sports Office. The research method used was a quantitative approach with correlational methods. The study population consisted of 38 employees, consisting of 28 structural civil servants and 10 functional civil servants, with a census sampling technique. Data were collected through questionnaires and analyzed using SmartPLS 3.2.2 software using a Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) approach. The results showed that competence has a positive and significant effect on work discipline and employee performance. Work discipline was also shown to have a positive and significant effect on employee performance. Furthermore, work discipline acts as a mediating variable, strengthening the relationship between competence and performance. The conclusion of this study states that increasing employee competence accompanied by the implementation of good work discipline can significantly improve employee performance. Keywords: Competence, Work Discipline, Employee Performance, Civil Servants, SEM-PLS